Building a Digital Learning Culture; Strategic Educational Leadership in Smart School Ecosystems - Mehmood Mustafa (Yayasan Avicenna, 2025)
In the era of rapidly evolving educational technologies, strategic leadership plays a crucial role in cultivating a sustainable digital learning culture within smart school ecosystems. This study aims to investigate how educational leaders in Pakistani schools navigate the challenges and leverage opportunities in building a digitally enriched learning environment. Employing a qualitative case study approach, data were collected through semi-structured interviews with principals, ICT coordinators, and teachers in five smart schools across three major cities in Pakistan: Lahore, Islamabad, and Karachi. Thematic analysis revealed four key leadership strategies contributing to digital transformation: vision-driven leadership, capacity building through continuous professional development, infrastructure mobilization, and fostering digital citizenship among students and staff. The findings highlight that strategic alignment between policy, pedagogy, and digital innovation significantly enhances school readiness for smart learning integration. However, systemic constraints such as inequitable access to devices, digital literacy gaps, and resistance to pedagogical change remain key barriers. This study contributes to the growing discourse on digital leadership by offering a contextualized framework for educational leaders in developing countries. The paper concludes with policy recommendations for building resilient digital learning ecosystems through adaptive leadership, stakeholder engagement, and inclusive digital planning.